The effect of decision-making infusion strategy on pre-service biology education teachers’ self-efficacy - Hikmah Buroidah; Bea Hana Siswati; Wachidah Hayuana (Universitas Negeri Jakarta, 2026)
Teacher self-efficacy is essential for effective teaching, yet many pre-service teachers still lack confidence in managing classrooms, selecting instructional strategies, and engaging students. This suggest that they need for an instructional approach that can strengthen their pedagogical decision-making. To address this issue, the Decision-Making Infusion Strategy (DMIS) is introduced as an innovative learning strategy integrated into the teacher education curriculum. This study aims to examine the effect of the Decision-Making Infusion Strategy (DMIS) on the self-efficacy of pre-service biology teachers, particularly in making pedagogical decisions related to classroom management, instructional strategies, and student engagement. The study employed an explanatory sequential mixed-methods design, in which DMIS was implemented as an instructional intervention during a pedagogy course. Quantitative data were collected using a Teacher Self-Efficacy Scale (TSES) adapted from Tschannen-Moran and Hoy, while qualitative data were obtained through semi-structured interviews. Quantitative data were analyzed using a paired-sample t-test, whereas qualitative data were analyzed using thematic analysis. The results showed a significant increase in self-efficacy scores following the DMIS intervention (p < 0.05). Qualitative findings further supported these results by identifying three key contributions of DMIS in strengthening pre-service teachers’ self-efficacy: (1) developing decision-making competence, (2) shifting from theoretical to reflective practice, and (3) mastery of pedagogical knowledge. These findings indicate that DMIS is effective in enhancing pre-service teachers’ self-efficacy and suggest that integrating DMIS into teacher education curricula can better prepare future biology teachers for classroom challenges. Future studies should apply experimental design with larger samples to confirm the longterm impact of DMIS on teacher development.